Contamination assessment, source apportionment and health risk assessment of heavy metals in paddy soils of Jiulong River Basin, Southeast China. Issue 26 (13th May 2019) - Huang, Huabin; Lin, Chengqi; Yu, Ruilian; Yan, Yu; Hu, Gongren; Li, Huojin
Abstract : APCS-MLR and dose–response model were combined to identify the sources and human health risks of heavy metals in paddy soils. Abstract : To trace the sources and evaluate the health risks of heavy metals in paddy soils of Jiulong River Basin, seventy-one samples of paddy soils were collected in July 2017. The heavy metals contents were determined using inductively coupled plasma mass spectrometry (ICP-MS) and atomic fluorescence spectrophotometry (AFS). The geo-accumulation index ( I geo ) and potential ecological risk index (RI) methods were applied to evaluate the contamination of heavy metals, principal component analysis (PCA) and absolute principal component scores-multiple linear regression (APCS-MLR) were applied to trace the sources, and dose–response model was applied to assess the health risks to the human body. The results indicated that the paddy soils were moderately to heavily polluted by Cd and slightly polluted by Hg, Pb, As and Zn. Heavy metals in paddy soils presented considerable to high potential ecological risk, mostly contributed by Cd and Hg with contribution rates of 59.4% and 26.2%, respectively. The heavy metals contaminating paddy soils were derived from natural sources, agricultural activities, industrial discharge, coal combustion and unidentified sources, with source contribution rates of 31.37%, 24.87%, 19.65%, 18.05% and 6.06%, respectively. The heavy metals in paddy soils presented carcinogenic risks which humans can tolerate and no non-carcinogenic risks. The total non-carcinogenic risks mainly derived from agricultural activities and coal combustion, with contribution rates of 62.16% and 20.21%, respectively, while the total carcinogenic risks mainly derived from natural sources and industrial discharge, with contribution rates of 51.17% and 18.98%, respectively.